Greek gods and heroes - Graves, Robert, 1895-1985 (RosettaBooks, 2014)
A retelling of the greatest myths and legends of the ancient Greek gods and heroes for readers of all ages by a celebrated historical novelist. In the ancient past, the Gods and Goddesses of ancient Greece lived on Mount Olympus and ruled the world of mortals. Famous heroes shaped the course of history, beautiful women drew the gazes of gods and men alike, and the gods were both fickle in their favors and breathtakingly generous to those they smiled upon. From Midas' tragic gift to the exploits of Hercules and the curse of Pandora, renowned classicist and historical novelist Robert Graves brings the legends of ancient Greece to life in a lively, accessible way that's sure to appeal to everyone; from children to adults, and from casual readers to serious scholars.